2019
DOI: 10.1111/jpi.12596
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SERPINA3N‐dependent neuroinflammation is essential for melatonin to ameliorate trimethyltin chloride–induced neurotoxicity

Abstract: Trimethyltin chloride (TMT) is a potent neurotoxin that causes neuroinflammation and neuronal cell death. Melatonin is a well‐known anti‐inflammatory agent with significant neuroprotective activity. Male C57BL/6J mice were intraperitoneally injected with a single dose of melatonin (10 mg/kg) before exposure to TMT (2.8 mg/kg, ip). Thereafter, the mice received melatonin (10 mg/kg, ip) once a day for another three consecutive days. Melatonin dramatically alleviated TMT‐induced neurotoxicity in mice by attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 67 publications
3
52
0
Order By: Relevance
“…Recently it has been demonstrated that melatonin acts through the Nrf2 pathway and prevents the decline of antioxidant enzyme activities during brain pathological conditions (Moezi et al, 2011;Mendez-David et al, 2015;Herrera-Arozamena et al, 2020;Zhi W. et al, 2020), supporting our results that endogenous melatonin counterbalances the oxidative stress by boosting the body antioxidants system via its receptors. Our results are also in agreement with growing evidence that melatonin enhances HO-1 expression via NF-κB, p38 MAPK, and Nrf2 cascade signaling mechanism (Santofimia-Castaño et al, 2015;Yu et al, 2017;Shah et al, 2017;Ma et al, 2018;Zhao et al, 2018;Rehman et al, 2019;Xi et al, 2019;García et al, 2020;Hein et al, 2020;Zhou et al, 2020;Zhi W. et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Recently it has been demonstrated that melatonin acts through the Nrf2 pathway and prevents the decline of antioxidant enzyme activities during brain pathological conditions (Moezi et al, 2011;Mendez-David et al, 2015;Herrera-Arozamena et al, 2020;Zhi W. et al, 2020), supporting our results that endogenous melatonin counterbalances the oxidative stress by boosting the body antioxidants system via its receptors. Our results are also in agreement with growing evidence that melatonin enhances HO-1 expression via NF-κB, p38 MAPK, and Nrf2 cascade signaling mechanism (Santofimia-Castaño et al, 2015;Yu et al, 2017;Shah et al, 2017;Ma et al, 2018;Zhao et al, 2018;Rehman et al, 2019;Xi et al, 2019;García et al, 2020;Hein et al, 2020;Zhou et al, 2020;Zhi W. et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…BTBR/R mice brains showed increased Serpina3n mRNA expression: intensely in the cerebral cortex, hippocampus, and amygdala; weakly in the striatum. Together with the transcriptomic data showing the enrichment of the immune signaling pathways in BTBR/R mice DEGs, we suggest that these brain regions in BTBR/R mice may have increased neuroinflammatory responses, as reported in other neurological disorders (Switonski et al, 2015;Vanni et al, 2017;Xi et al, 2019). Upregulated DEG Lpl encodes lipoprotein lipase that is the key enzyme in triglyceride metabolism.…”
Section: Altered Spatial Expression Patterns Of Deg Mrnas In the Btbrsupporting
confidence: 74%
“…Scg5 (secretogranin V, 7B2) encodes a secreted chaperone protein that prevents the aggregation of other secreted proteins inside of secretory vesicles, and its KO mice show a number of endocrine abnormalities (Bartolomucci et al, 2011). Serpina3n (Serine protease inhibitor A3N) encodes a secretory serine protease inhibitor that mediates neuroinflammation (Xi et al, 2019) and is upregulated in various neurological diseases (Switonski et al, 2015;Vanni et al, 2017). Nudt19 (Nucleoside diphosphate linked moiety X [Nudix]-type motif 19) encodes a peroxysomal nudix hydrolase (Carreras-Puigvert et al, 2017) that exerts a CoA diphosphohydrolase activity in the kidney (Shumar et al, 2018) and its KO mice caused a significant decrease in total CoA levels in the kidney (Shumar et al, 2018).…”
Section: Similarity In Degs Between Two Sublines Of Btbr: Btbr/r and mentioning
confidence: 99%
“…Besides, TMT has good lipophilicity and high affinity with hemoglobin in blood, and can be accumulated in human bodies [2]. After TMT treatment, mice can show agitation, aggressive behavior, learning and memory dysfunction [4][5][6][7]. According to reports, TMT can selectively damage the limbic system, especially in the prefrontal cortex, hippocampus and other brain regions and lead to the dysfunction and apoptosis in these regions, which are closely related to learning and memory function, suggesting that TMT-induced learning and memory dysfunction have a special correlation with such selective effect [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of nervous system damage induced by TMT include apoptosis, inflammatory response, oxidative damage, glutamate excitability, etc. [6,[10][11]. However, the exact mechanisms of TMT-induced widely nervous system damage are not fully clear.…”
Section: Introductionmentioning
confidence: 99%